The Effectiveness of an Educational Program Based on Semiotic Theory in Developing Critical Skills Among Students of Arabic Language Departments in Colleges of Basic Education (Journal of the College of Basic Education, 2025)
The effectiveness of the educational program is defined according to the semiotic theory in the development of critical skills among students of the Arabic language departments in the faculties of basic education.To achieve the first research goal, the researcher followed the descriptive curriculum procedures, as the researcher built the educational program according to the semiotic theory to teach the subject (modern literature) to fourth-grade students in the Arabic language department. To achieve the second objective of the research, the researcher relied on an experimental design with partial control: the design of the experimental and control groups and the dimensional test. The research community consisted of the faculties of basic education in Iraqi universities, numbering (13) faculties, and the researcher deliberately chose the Mustansiriya Faculty of basic education as a sample for his research, which amounted to (80) students, from the fourth grade students divided into two randomly selected divisions, Hall ( 1 ) represented the experimental group with (40) students, while the Triangle of Hall (2) the control group with (40) students. The researcher rewarded him among the students of the two research groups in the following variables: (literature grades in the previous stage, language ability test, mental motivation scale). As for the research tool, it was a test prepared by the researcher according to bloom's six levels (remembering, understanding, Application, Analysis, composition, evaluation), as it included (20) paragraphs, from the questions of the specific article. The researcher verified the truthfulness and consistency of the test, extracted the coefficient of difficulty of its paragraphs and the discriminatory force of it after applying it to a statistical sample of (141) students of the fourth stage at the Faculty of basic education Aziziya and Diyala, and for the objectivity of the researcher verified the truthfulness of the test after she presented it to a group of arbitrators. The same researcher studied the students of the two groups, the experimental in the proposed program, and the control in the regular program during the duration of the experiment, in the first course of the academic year. 2025-2024 After the end of the experiment, the researcher applied the test to the students of the two research groups (experimental and control). To statistically process the data, the researcher used the Levene test to verify the homogeneity of the two groups, the T-test of two independent samples, the alpha-cronbach equation, the Pearson correlation coefficient, the difficulty coefficient equation and the discriminant strength equation, the macjugian law of effectiveness, and the effectiveness size equation (ETA square).